2021
DOI: 10.1111/maps.13620
|View full text |Cite
|
Sign up to set email alerts
|

The polymict carbonaceous breccia Aguas Zarcas: A potential analog to samples being returned by the OSIRIS‐REx and Hayabusa2 missions

Abstract: On April 23, 2019, a meteorite fall occurred in Aguas Zarcas, Costa Rica. According to the Meteoritical Bulletin, Aguas Zarcas is a brecciated CM2 chondrite dominated by two lithologies. Our X‐ray computed tomography (XCT) results show many different lithologies. In this paper, we describe the petrographic and mineralogical investigation of five different lithologies of the Aguas Zarcas meteorite. The bulk oxygen isotope compositions of some lithologies were also measured. The Aguas Zarcas meteorite is a brecc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 65 publications
(94 reference statements)
8
44
0
Order By: Relevance
“…The recent discovery of pyroxene brecciated boulders on the surface of Bennu has confirmed this hypothesis (DellaGiustina et al, 2021). Kerraouch et al (2021) concluded that “the different lithologies of the fresh AZ breccia, which represent different levels of hydration and heating, are good analogs for the types of materials that will be returned from asteroids Bennu and Ryugu.” More recently, analyses of Ryugu grains have shown that their spectra are different from the ones of CM meteorites and more similar to the ones of CI chondrites (Pilorget et al., 2021; Yada et al, 2021). However, the remote sensing spectrum of asteroid Bennu measured by the OTES instrument onboard OSIRIS‐REx (Hamilton et al, 2021) has shown that Bennu is closer to CM chondrites.…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery of pyroxene brecciated boulders on the surface of Bennu has confirmed this hypothesis (DellaGiustina et al, 2021). Kerraouch et al (2021) concluded that “the different lithologies of the fresh AZ breccia, which represent different levels of hydration and heating, are good analogs for the types of materials that will be returned from asteroids Bennu and Ryugu.” More recently, analyses of Ryugu grains have shown that their spectra are different from the ones of CM meteorites and more similar to the ones of CI chondrites (Pilorget et al., 2021; Yada et al, 2021). However, the remote sensing spectrum of asteroid Bennu measured by the OTES instrument onboard OSIRIS‐REx (Hamilton et al, 2021) has shown that Bennu is closer to CM chondrites.…”
Section: Introductionmentioning
confidence: 99%
“…AZ is highly brecciated with multiple lithologies that are thought to be the result of different degrees of aqueous alteration and impact modi cation 7 . Nevertheless, the two distinct types of AZ in a small volume cannot be explained as products of different degrees of aqueous alteration or heterogeneous shocking effect within such close (mm) proximity, but rather suggest necessary transport of the compact fragments into an undeformed lithology before nal lithi cation.…”
Section: Discussionmentioning
confidence: 99%
“…We selected Aguas Zarcas (hereafter AZ), a CM2 meteorite that is similar in composition to asteroid Bennu based on the spectral data 6 . AZ is a breccia containing several lithologies such as brecciated CM, C1, C1/2, and metal-rich ones, which are the result of collisions and aqueous alteration 7 . We used mechanical disintegration to characterize the rock, followed by X-ray microtomography (μCT) and scanning electron microscopy (SEM) (see Methods), then compared our data with the observations of Bennu.…”
Section: Introductionmentioning
confidence: 99%
“…The brecciated CM2 chondrite LON 94101 contains clasts of C1 material, including highly unusual lithologies, one containing 46 vol% carbonate, and one containing ~mm-sized laths of pyrrhotite, suggesting heterogeneous fluid compositions (Lindgren et al, 2013). The CM2 meteorite Aguas Zarcas is a breccia containing type 1 material composed of phyllosilicates, magnetite, sulfides, and carbonates (Kerraouch et al, 2021); the phyllosilicate composition is similar to that of inclusion 91A in Almahatta Sitta (see "Ureilites" section below; . The CR chondrites contain dark inclusions (<8 area %; Kallemeyn et al, 1994) that record variable degrees of alteration and which can resemble CI-like clasts (Weisberg et al, 1993), although the oxygen isotope composition of these clasts falls closer to CM chondrites (Endress, Keil, Bischoff, et al, 1994;.…”
Section: Carbonaceous Chondritesmentioning
confidence: 99%